Atopy is a significant risk factor for exercise-induced bronchoconstriction in elite summer sport athletes - Holzer, K.; Anderson, S. (Australian conference of science and medicine in sport 2004. Hot topics from the Red Centre, 2004)
It is well known that atopy is a positive risk factor for asthma, however the actual relationship between atopy and Exercise-induced Bronchoconstriction (EIB) as defined by a positive eucapnic voluntary hyperpnoea (EVH) challenge or mannitol challenge in elite summer sport athletes has yet to be defined. Aim: To assess the relationship between atopy and the EVH and mannitol challenges in elite summer sport athletes. Methods: 50 elite summer sport athletes (15M,35F age), with or without known EIB underwent SST to 9 common airborne allergens and on separate occasions, an EVH test a mannitol challenge test.A positive SST was a wheal diameter>/=3mm. A positive EVH test was a fall in FEV1>/=10%. A positive mannitol test was a fall in FEV1>/=10%. Results: All 50 subjects completed each test. 37 subjects had one or more positive SST. Twenty-five of the 50 subjects (50%) had a positive EVH test, with a mean fall of 25.4±15%, and 26 (52%) recorded a positive mannitol test with a geometric mean (95%CI) PD10 of 202mg (134,300). Of the 37 subjects recording at least one positive SST, 23 had a positive EVH challenge (mean fall in FEV1:26.5 ± 15%) and 24 a positive mannitol challenge.(geometric mean (95%CI) PD10: 193.6mg (126.1, 297.1) ). A significant relationship was seen between the presence of a positive response to the EVH and mannitol challenge tests and each of the following allergens: house dust mite, couch grass pollen, birch pollen, rye pollen, and grass pollen mix. Conclusion: Atopy, either perennial or seasonal, appears to be a risk factor for the development of EIB in elite summer sport athletes.